Effect of Induction Chemotherapy in Nasopharyngeal Carcinoma: An Updated Meta-Analysis - Yang, Shan-Shan; Guo, Jian-Gui; Liu, Jia-Ni; Liu, Zhi-Qiao; Chen, En-Ni; Chen, Chun-Yan; OuYang, Pu-Yun; Han, Fei; Xie, Fang-Yun (Frontiers in Oncology, 2021)
Background Previous meta-analysis had evaluated the effect of induction chemotherapy in nasopharyngeal carcinoma. But two trials with opposite findings were not included and the long-term result of another trial significantly differed from the preliminary report. This updated meta-analysis was thus warranted. Methods Literature search was conducted to identify randomized controlled trials focusing on the additional efficacy of induction chemotherapy in nasopharyngeal carcinoma. Trial-level pooled analysis of hazard ratio (HR) for progression free survival and overall survival and risk ratio (RR) for locoregional control rate and distant control rate were performed. Results Twelve trials were eligible. The addition of induction chemotherapy significantly prolonged both progression free survival (HR=0.68, 95% confidence interval [CI] 0.60–0.76, p<0.001) and overall survival (HR=0.67, 95% CI 0.54–0.80, p<0.001), with 5-year absolute benefit of 11.31% and 8.95%, respectively. Locoregional (RR=0.80, 95% CI 0.70–0.92, p=0.002) and distant control (RR=0.70, 95% CI 0.62–0.80) rates were significantly improved as well. The incidence of grade 3–4 adverse events during the concurrent chemoradiotherapy was higher in leukopenia (p=0.028), thrombocytopenia (p<0.001), and fatigue (p=0.038) in the induction chemotherapy group. Conclusions This meta-analysis supported that induction chemotherapy could benefit patients with nasopharyngeal carcinoma in progression free survival, overall survival, locoregional, and distant control rate.